Bis{2-[bis(2-hydroxyethyl)amino]acetato-kappa O-3,N,O `}zinc(II) - Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the crystal structure of the zinc(II) complex of bicine, [Zn(C6H12NO4)(2)], the deprotonated amino acid O,N,O'-chelates to the metal atom through a carboxylate O atom, a hydroxy O atom and the N atom, the three atoms occupying fac positions of the distorted octahedron surrounding the metal atom. The metal atom lies on a center of inversion. The uncoordinated carboxylate O atom is hydrogen bonded to the hydroxy groups of adjacent molecules, these two hydrogen bonds leading to the formation of a three-dimensional network.